Conductive acrylate adhesive and application thereof

By using solvent-free bioacrylate adhesive composition, conductive tape with excellent conductivity and adhesive properties is prepared, which solves the problem that existing conductive tapes are difficult to meet environmental protection and sustainable development requirements, and achieves efficient bonding and electromagnetic shielding effects for electronic products.

CN119842344APending Publication Date: 2025-04-18TESA SE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311336340.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-16
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The conductive tape prepared by existing solvent-based acrylate adhesives is difficult to meet the requirements of environmental protection and sustainable development, and its conductive and adhesive properties are not sufficient to meet the needs of modern electronic products.

Method used

Using a solvent-free bio-acrylate adhesive composition, including acrylate monomers, initiators, crosslinkers, tackifiers and conductive fillers, conductive tapes with excellent conductivity and adhesive properties are prepared by optimizing the adhesive formulation and using sustainable materials.

Benefits of technology

It realizes that the conductive tape has excellent conductivity and adhesive properties while meeting the requirements of environmental protection and sustainable development, and is suitable for the bonding applications of modern electronic products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004495932310000021
    Figure BDA0004495932310000021
  • Figure BDA0004495932310000022
    Figure BDA0004495932310000022
  • Figure BDA0004495932310000023
    Figure BDA0004495932310000023
Patent Text Reader

Abstract

The invention relates to a conductive acrylate adhesive and application thereof. Specifically, the invention discloses a conductive acrylate adhesive, the conductive adhesive and a conductive adhesive tape with excellent conductivity and adhesion performance are obtained by selecting an optimized acrylate monomer, and meanwhile, all structures of the acrylic conductive adhesive tape can be made of sustainable materials (bio-based raw materials or materials recycled after consumption). The adhesive has excellent adhesion performance and conductivity, and can fully meet the requirements of environmental protection and sustainable development.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of adhesive tapes, and in particular to sustainably sourced conductive acrylate adhesives and their applications. Background Art

[0002] With the continuous development of science and technology, electronic products have become rapidly popular in daily life. The more compact the design of electronic components, the greater the possibility of electromagnetic interference, short circuits and failures. For this problem, using conductive tape to ground and shield electronic components can minimize this interference.

[0003] Currently, the conductive tapes widely used in electronic products are mostly prepared from solvent-based acrylic adhesives. Although they can meet the needs of conductivity and adhesion, due to the use of solvents, the conductive tapes often fail to meet the requirements of environmental protection and sustainable development.

[0004] As countries have higher and higher requirements for environmental protection and sustainability, the conductive tape prepared by the above solvent-based acrylic adhesive has become increasingly difficult to meet market demand. In addition to having good conductivity and bonding properties, the market demand for conductive tape also requires environmental protection and sustainability of the tape. Summary of the invention

[0005] The object of the present invention is to provide an acrylic adhesive and a conductive tape with excellent conductive properties, wherein the tape not only has excellent conductive properties and adhesive properties, but also all structures of the acrylic conductive tape can be made of sustainable materials (bio-based raw materials or post-consumer recycled materials). Therefore, the tape can fully meet the requirements of environmental protection and sustainable development while having excellent adhesive properties and conductive properties.

[0006] In a first aspect of the present invention, a conductive adhesive composition is provided, the composition comprising the following components:

[0007] 1) Acrylate monomer 50-75 parts by weight

[0008] 2) Initiator 0.05-0.5 parts by weight

[0009] 3) 0.1-2 parts by weight of crosslinking agent

[0010] 4) 8-40 parts by weight of a tackifier, and

[0011] 5) 5-30 parts by weight of conductive filler;

[0012] The acrylate monomer comprises a first monomer and a second monomer;

[0013] The first monomer has a structure shown in Formula I:

[0014]

[0015] Wherein, R1 is H or C1-C3 alkyl;

[0016] R2 is a C6-C8 alkyl group, and the C6-C8 alkyl group is a straight-chain alkyl group;

[0017] The second monomer is selected from the following group: a compound represented by formula II, a compound represented by formula III, or a combination thereof;

[0018]

[0019] R4 is selected from the following groups: H, unsubstituted or C1-C3 alkyl-substituted C3-C8 cycloalkyl, C1-C6 alkyl; R5 is a 4-8 membered heterocyclic group containing 1, 2 or 3 heteroatoms selected from N, O or S;

[0020] Furthermore, based on the total weight of the acrylic ester monomer, the content of the first monomer is 55-75 wt %.

[0021] In another preferred embodiment, R1 is selected from the following group: H, methyl, ethyl, propyl, isopropyl.

[0022] In another preferred embodiment, R2 is selected from the following group: n-hexyl, n-heptyl, n-octyl.

[0023] In another preferred embodiment, the first monomer is selected from the following group:

[0024]

[0025] In another preferred embodiment, the second monomer is selected from the following group:

[0026]

[0027]

[0028] In another preferred embodiment, the cross-linking agent is selected from the following group: ethylene glycol dimethacrylate, 1,6-hexanediol diacrylate, neopentyl glycol polymethyl ethylene oxide diacrylate;

[0029] The tackifier is selected from the group consisting of rosin resin, terpene resin, and C5-C9 petroleum resin;

[0030] The conductive filler is selected from the following group: particles of nickel, iron, chromium, cobalt, aluminum, copper, silver, gold, vanadium, tin, titanium, or niobium or their alloys; solder; stainless steel; metal oxides; carbon black; metal-coated particles obtained by coating the surface of metal-coated polymer microbeads or glass microbeads; and conductive particles of other metals coated on the surface of metal particles.

[0031] A second aspect of the present invention provides a conductive tape, the tape comprising the following structures in sequence:

[0032] 1) an optional first release film;

[0033] 2) a first adhesive layer;

[0034] 3) substrate;

[0035] 4) a second adhesive layer;

[0036] 5) an optional second release film;

[0037] The first adhesive layer and the second adhesive layer are made of the conductive adhesive composition described in the first aspect of the present invention.

[0038] In another preferred embodiment, the thickness of the tape is 20-150 μm.

[0039] In another preferred embodiment, the peeling force of the adhesive tape is ≥8.5N / cm; and / or

[0040] The contact resistance of the adhesive tape is ≤0.06Ω.

[0041] The third aspect of the present invention provides the use of the conductive tape according to the second aspect of the present invention for bonding components in electronic products.

[0042] It should be understood that within the scope of the present invention, the above-mentioned technical features of the present invention and the technical features specifically described below (such as embodiments) can be combined with each other to form a new or preferred technical solution. Due to space limitations, they will not be described one by one here. DETAILED DESCRIPTION

[0043] After long-term and in-depth research, the inventors have obtained an acrylate adhesive and a conductive tape with excellent conductive and adhesive properties by optimizing the adhesive formula (such as the preferred acrylate monomer type), and all structures of the conductive tape can be made of sustainable materials (bio-based materials or post-consumer recycled materials), so it can fully meet the requirements of environmental protection and sustainable development while having excellent adhesive and conductive properties. On this basis, the inventors have completed the present invention.

[0044] the term

[0045] In the present invention, unless otherwise specified, the terms used have the general meanings well known to those skilled in the art.

[0046] In the present invention, "C1-C6 alkyl" refers to a straight or branched alkyl group including 1 to 6 carbon atoms, such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, neopentyl, tert-pentyl, or the like. The term "C1-C3 alkyl" has a similar meaning.

[0047] In the present invention, the term "C3-C8 cycloalkyl" refers to a cyclic alkyl group having 3 to 8 carbon atoms in the ring, including but not limited to cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl and the like.

[0048] In the present invention, the term "heterocyclic group" refers to a 4-8 membered heterocyclic group containing 1, 2 or 3 heteroatoms selected from N, O and S, including (but not limited to) the following groups:

[0049] As used herein, the term "comprising" or "including (comprising)" may be open, semi-closed and closed. In other words, the term also includes "consisting essentially of" or "consisting of".

[0050] The English abbreviations used in this article have the following meanings:

[0051] PET: Polyethylene terephthalate

[0052] PCR: Post Customer Recycled, i.e. post-consumer recycled plastic

[0053] PCR PET: Post-consumer recycled PET

[0054] SUS: Stainless steel

[0055] Bio-based materials refer to a new type of materials that are manufactured through biological, chemical, physical and other means using renewable materials, including grains, legumes, straw, trees, bamboo powder, animal fur waste, etc. as raw materials. Basic chemicals such as organic acids, bio-alcohols, olefins, alkanes, etc. can be obtained through this process, as well as plastic products such as bio-fibers, bio-plastics, bio-based rubbers, and sugar engineering products. According to product attributes, bio-based materials can be divided into bio-based polymers, bio-based plastics, bio-based fibers, bio-based rubbers, bio-based coatings, bio-based material additives, bio-based composite materials and products made from various bio-based materials, etc., which are green, environmentally friendly, renewable raw materials and biodegradable.

[0056] PCR material is a kind of "recycled plastic", and its full name is Post-Consumer Recycled material, which means post-consumer recycled material. Waste plastics usually generated after circulation, consumption, and use can be turned into extremely valuable industrial production raw materials through physical or chemical recycling, thus realizing resource recycling and reuse. For example, recycled materials such as PET, PE, PP, and HDPE come from waste plastics generated by daily lunch boxes, shampoo bottles, mineral water bottles, washing machine barrels, etc., which can be used to make new plastic raw materials after reprocessing. Post-consumer recycled (PCR) plastics have become one of the important directions to reduce plastic environmental pollution and help the chemical industry move towards "carbon neutrality".

[0057] Adhesives

[0058] In response to the national requirements on environmental protection and sustainable development, the present invention provides a solvent-free acrylate adhesive with sustainable raw materials, the adhesive comprising the following components:

[0059] Preferably Better Acrylate Monomer 50-75 parts by weight 52-70 parts by weight 54-65 parts by weight Initiator 0.05-0.5 parts by weight 0.1-0.3 parts by weight 0.2 parts by weight Crosslinking agent 0.1-2 parts by weight 0.5-1.5 parts by weight 0.8 parts by weight Tackifier 8-40 parts by weight 10-35 parts by weight 14-30 parts by weight Conductive filler 5-30 parts by weight 10-25 parts by weight 15-20 parts by weight.

[0060] In another preferred embodiment, the acrylate monomer is a bio-based material.

[0061] In another preferred embodiment, the viscosity enhancing agent is a bio-based material.

[0062] In another preferred embodiment, the adhesive contains no solvent.

[0063] In another preferred embodiment, the acrylate monomer comprises a first monomer and a second monomer;

[0064] The first monomer has a structure shown in Formula I:

[0065]

[0066] Wherein, R1 is H or C1-C3 alkyl;

[0067] R2 is a C6-C8 alkyl group, and the C6-C8 alkyl group is a straight-chain alkyl group;

[0068] The second monomer is selected from the following group: a compound represented by formula II, a compound represented by formula III, or a combination thereof;

[0069]

[0070] R4 is selected from the following groups: H, unsubstituted or C1-C3 alkyl-substituted C3-C8 cycloalkyl, C1-C6 alkyl;

[0071] R5 is a 4-8 membered heterocyclic group containing 1, 2 or 3 heteroatoms selected from N, O or S;

[0072] Furthermore, based on the total weight of the acrylic ester monomer, the content of the first monomer is 55-75 wt %.

[0073] In another preferred embodiment, R1 is selected from the following group: H, methyl.

[0074] In another preferred embodiment, R2 is n-hexyl.

[0075] In another preferred embodiment, R4 is selected from the following groups: H, C3-C8 cycloalkyl substituted with C1-C3 alkyl, C1-C6 alkyl.

[0076] In another preferred embodiment, based on the total weight of the acrylic ester monomer, the content of the first monomer is 60-70 wt %, preferably 65-69 wt %.

[0077] In another preferred embodiment, the weight ratio of the first monomer to the second monomer is 1.3-3, preferably 1.5-2.5, and more preferably 1.7-2.3.

[0078] In another preferred embodiment, the first monomer is selected from the following group:

[0079]

[0080] In another preferred embodiment, the second monomer is selected from the following group:

[0081]

[0082] In another preferred embodiment, the initiator is PI-819.

[0083] In another preferred embodiment, the cross-linking agent is selected from the following group: ethylene glycol dimethacrylate, 1,6-hexanediol diacrylate, neopentyl glycol polymethyl ethylene oxide diacrylate.

[0084] In another preferred embodiment, the tackifier is selected from the following group: rosin resin, terpene resin, C5-C9 petroleum resin.

[0085] In another preferred embodiment, the conductive filler is selected from the following group: particles of nickel, iron, chromium, cobalt, aluminum, copper, silver, gold, vanadium, tin, titanium, or niobium or their alloys; solder; stainless steel; metal oxides; carbon black; metal-coated particles obtained from the surface of metal-coated polymer microbeads and glass microbeads; and conductive particles of other metals coated on the surface of metal particles.

[0086] In another preferred embodiment, based on the total weight of the adhesive, the content of the acrylate monomer is 50-75wt%, preferably 52-70wt%, and more preferably 54-65wt%.

[0087] In another preferred embodiment, based on the total weight of the adhesive, the content of the initiator is 0.05-0.5wt%, preferably 0.1-0.3wt%, and more preferably 0.2wt%.

[0088] In another preferred embodiment, based on the total weight of the adhesive, the content of the crosslinking agent is 0.1-2 wt %, preferably 0.5-1.5 wt %, and more preferably 0.8 wt %.

[0089] In another preferred embodiment, based on the total weight of the adhesive, the content of the tackifier is 8-40wt%, preferably 10-35wt%, and more preferably 14-30wt%.

[0090] In another preferred embodiment, based on the total weight of the adhesive, the content of the conductive filler is 5-30wt%, preferably 10-25wt%, and more preferably 15-20wt%.

[0091] In another preferred embodiment, based on the total weight of the adhesive being 100wt%, the weight of the acrylate monomer, initiator, crosslinker, tackifier and conductive filler is ≥95wt%, preferably ≥97wt%, more preferably ≥99wt%, and preferably 100wt%.

[0092] In another preferred embodiment, the adhesive composition is of bio-based origin.

[0093] In another preferred embodiment, the bio-based content of the adhesive is 40-80%, preferably 50-80%, and more preferably 60-80%.

[0094] Adhesive tape and method for preparing the same

[0095] Based on the above-mentioned solvent-free bio-based acrylate adhesive of the present invention, the present invention also provides a bio-based conductive tape, wherein the tape comprises the following structure:

[0096] 1) an optional first release film;

[0097] 2) a first adhesive layer;

[0098] 3) substrate;

[0099] 4) a second adhesive layer;

[0100] 5) Optional second release film.

[0101] In another preferred embodiment, the substrate is PET. In order to increase the conductivity of the adhesive tape, the substrate can be a conductive substrate, and the conductive substrate is a PET fiber coated with a metal. The metal used for the coating is preferably selected from nickel, copper, nickel alloys and copper alloys. Preferred nickel alloys are, for example, nickel-vanadium alloys (NiV), nickel-chromium alloys (NiCr), nickel-tin alloys (NiSn), nickel-phosphorus alloys (NiP), nickel-titanium alloys (NiTi) and nickel-niobium alloys (NiNb). In a preferred embodiment of the adhesive tape of the present invention, the PET fiber has a multilayer metal coating, wherein the nickel undercoat is coated with nickel-plated copper foil, thereby producing a structure of PET-Ni-Cu-Ni. The metal coating can be applied in particular by electroplating. In order to give the adhesive tape the necessary stability, the substrate is preferably a woven fabric or a non-woven fabric.

[0102] In another preferred embodiment, the substrate is PCR PET. The PCR PET is composed of at least 85% by weight of post-consumer recycled PET based on the total weight of PET. Preferably, the PET fiber is composed of at least 90% by weight of post-consumer recycled PET. More preferably, the PET fiber is composed of at least 99% by weight of post-consumer recycled PET. Particularly preferably, the PET fiber is 100% by weight of post-consumer recycled PET.

[0103] In another preferred embodiment, the substrate of the first release film and / or the second release film is a PET film.

[0104] In another preferred embodiment, the substrate of the first release film and / or the second release film is a PCR PET film, and the PET film is composed of at least 85 wt%, preferably at least 90 wt%, more preferably at least 99 wt%, and particularly preferably 100 wt% of post-consumer recycled PET.

[0105] In another preferred embodiment, at least 50% by weight, preferably at least 65% by weight, particularly preferably at least 70% by weight of the first adhesive layer and / or the second adhesive layer are obtained from renewable raw materials, the weight % being based on the total weight of the adhesive and the adhesive resin. Monomers with a high proportion of biochar have proven to be particularly suitable, in particular 2-octyl acrylate, isobutyl acrylate and n-heptyl acrylate and mixtures thereof.

[0106] In addition to the adhesive, the adhesive layer also has at least one adhesive resin component that is different from the adhesive. It has been found that non-polar hydrocarbon resins, such as hydrogenated and non-hydrogenated polymers of dicyclopentadiene, non-hydrogenated, partially, selectively or fully hydrogenated hydrocarbon resins based on C5, C5 / C9 or C9 monomer streams, polyterpene resins based on α-pinene and / or β-pinene and / or δ-limonene can be advantageously used as the adhesive resin component of the adhesive layer. The above-mentioned adhesive resin components can be used alone or in combination. Both solid and liquid resins can be used at room temperature. In order to further increase the proportion of biochar, rosin resins and terpene resins are particularly preferred as adhesive resin components.

[0107] The adhesive tape according to the invention is intended in particular for electronic components which usually have a very compact structure. In order to adapt to the usually limited space conditions, the adhesive tape according to the invention is not only characterized by its high proportion of biochar, but also by its low thickness. In a preferred embodiment, the thickness of the adhesive tape according to the invention is 20 μm to 150 μm, preferably 30 μm to 125 μm. It was surprisingly shown here that despite the low thickness, good adhesive strength and a good electromagnetic interference shielding effect can be achieved.

[0108] In another preferred embodiment, the thickness of the tape is 20-150 μm, preferably 50-130 μm, and more preferably 80-125 μm.

[0109] In another preferred embodiment, the thickness of the substrate is 20-100 μm, preferably 30-80 μm.

[0110] In another preferred embodiment, the thickness of the first adhesive layer is 10-100 μm, preferably 10-50 μm, and more preferably 10-30 μm.

[0111] In another preferred embodiment, the thickness of the second adhesive layer is 10-100 μm, preferably 10-50 μm, and more preferably 10-30 μm.

[0112] In another preferred embodiment, the bio-based content of the adhesive tape is 40-80%, preferably 60-80%.

[0113] In the context of the present invention, it was surprisingly found that the mechanical and physical properties of the adhesive tapes of the present invention are comparable to those of conventional adhesive tapes based on fossil raw materials, in particular in terms of adhesive properties and electrical conductivity, despite the high proportion of biochar. In a preferred embodiment, the adhesive tape has a peel adhesion (peel strength) at 180° of ≥6 N / cm, preferably ≥7 N / cm, more preferably ≥8 N / cm, and most preferably ≥9 N / cm.

[0114] In addition to good adhesive properties, the adhesive tape of the present invention is also known for its electrical conductivity. In a preferred embodiment, the adhesive tape has a contact resistance of 0.005 to 0.06 Ω, preferably 0.01 to 0.05 Ω, measured according to MIL-DTL-83528C. In a further preferred embodiment, the adhesive tape has a surface resistance of 0.03 to 0.3 Ω, preferably 0.04 to 0.2 Ω, measured according to MIL-DTL-83528C.

[0115] In another preferred embodiment, the contact resistance of the tape is ≤0.06Ω, preferably ≤0.05Ω.

[0116] In another preferred embodiment, each layer structure of the adhesive tape is made of sustainable materials, and the sustainable materials are bio-based materials, post-consumer recycled materials (PCR) or a combination thereof.

[0117] application

[0118] The invention also provides the use of the conductive adhesive tape for bonding components in electronic products.

[0119] In another preferred embodiment, the electronic product is selected from the following group: a flexible printed circuit board, a display, a printed circuit board, a speaker, a camera element, an antenna, and an automotive electronic circuit board.

[0120] Compared with the prior art, the present invention has the following main advantages:

[0121] (1) By optimizing the monomer type and adding relatively less conductive filler, the conductive tape of the present invention obtains significantly excellent conductive properties and bonding properties;

[0122] (2) The conductive tape of the present invention can be made entirely of sustainable raw materials, which can achieve excellent adhesive and conductive properties while fully meeting the requirements of environmental protection and sustainable development.

[0123] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods for which specific conditions are not specified in the following examples are usually performed under conventional conditions or under conditions recommended by the manufacturer. Unless otherwise stated, percentages and parts are calculated by weight.

[0124] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein can be applied to the methods of the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only.

[0125] General raw materials

[0126] PCR PET: The PCR PET used in the present invention is selected from PCR PET having one of the following characteristics:

[0127] 1) 80μm thickness, 85% recycled content, derived from recycled plastic bottles;

[0128] 2) Thickness is 30μm, and the recycled material content is 90%, derived from recycled plastic bottles;

[0129] 3) 50 μm thickness, 100% recycled content, derived from recycled plastic bottles;

[0130] 4) Thickness is 23μm and the recycled material content is 100%, derived from recycled plastic bottles.

[0131] It should be understood that, compared with conventionally used PET (such as non-PCR PET), the PCR PET used in the present invention has comparable adhesive properties and conductive properties to the conductive tape, ie, has no negative effects.

[0132] Acrylate monomers: The acrylate monomers used in the present invention are selected from the following groups:

[0133]

[0134]

[0135] Crosslinking agent:

[0136]

[0137] Tackifier: The tackifier used in the present invention is selected from the following group:

[0138] Foral 85 Rosin resin, Tg 24°C, from DRT, France, 100% bio-based Dertophene T115 Terpene resin, Tg 66°C, from DRT, France, bio-based content 84%

[0139] Initiator: PI-819 (phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide), from Agenmon (Shanghai) Management Co., Ltd.

[0140] Conductive filler: Ni particles, particle size D50 is 5 μm, from Jiangxi Yuean New Materials Co., Ltd.

[0141] General test methods

[0142] Adhesion performance (peel force)

[0143] The peel force measurement is carried out in a test climate with a temperature of 23°C + / - 1°C and a relative air humidity of 50% + / - 5%. The samples are cut into a width of 20 mm and pasted on a steel plate (ASTM). The steel plate is cleaned and conditioned before measurement. To this end, the plate is first wiped with a solvent and then placed in the air for 5 minutes so that the solvent can evaporate. The side of the tape facing away from the test substrate is then covered with a 25 μm thick etched PET foil to prevent the sample from stretching during measurement. The specimen is then rolled onto the substrate. To this end, the tape is rolled back and forth 5 times with a 4 kg roller at a roller speed of 10 m / min. One minute after rolling, the plate is pushed into a specific bracket. The adhesion measurement is carried out using a Zwick tensile tester; the sample is peeled off at an angle of 180° at a speed of 300 mm / min. The measurement results are given in N / cm and are averaged from five individual measurements.

[0144] Conductive properties (contact resistance)

[0145] The contact resistance is measured in a test climate of 23°C + / - 1°C and 50% + / - 5% relative air humidity. The sample is cut into a size of 40mm*40mm and pasted on a gold-plated electrode plate. The electrode plate is cleaned and conditioned before measurement. To this end, the plate is first wiped with a solvent and then placed in the air for 5 minutes so that the solvent can evaporate. The sample is sandwiched between two electrode plates and the contact resistance is measured by using a Kiethely 580 micro-ohmmeter, and the average value is taken from five individual measurements.

[0146] Biobased Content

[0147] The samples were sent to BETA laboratory in the United States for testing according to ASTM-6866-21 method.

[0148] Example 1 Bio-based acrylate adhesive 1 and bio-based conductive tape 1

[0149] 1) Providing acrylate monomers, initiators, crosslinking agents, tackifiers and conductive fillers;

[0150] 2) mixing the acrylate monomer, initiator, crosslinking agent, tackifier and conductive filler to obtain the bio-based acrylate adhesive 1.

[0151] 3) providing the bio-based acrylate adhesive 1, a substrate, a first release film and a second release film;

[0152] 4) The bio-based acrylate adhesive 1 is applied to the substrate with a scraper and covered with the first release film. Then the substrate is irradiated under ultraviolet light. The irradiation conditions are: wavelength 365nm LED, intensity 0.5mW / cm 2, irradiation time 6 minutes. The aromatic crosslinkable group of the photoinitiator in the composition absorbs the energy of the ultraviolet light and excites free radicals, which initiates the double bond opening of the acrylate monomer to cause a chain polymerization reaction, so that the adhesive 1 is cured and a first adhesive layer with a thickness of 10 μm is obtained;

[0153] 5) The substrate surface of the adhesive tape not coated with the adhesive layer is coated again according to the above method, covered with a second release film after coating, and placed under the same ultraviolet irradiation to obtain a second adhesive layer with a thickness of 10 μm after curing.

[0154] The obtained bio-based conductive tape 1 has the following structure in sequence:

[0155] 1) The first release film: made of PCR PET, with a thickness of 50 μm;

[0156] 2) First adhesive layer: obtained from bio-based acrylate adhesive 1, with a thickness of 10 μm and a bio-based content of 75%;

[0157] 3) Substrate: Material is PCR PET, thickness is 30μm;

[0158] 4) Second adhesive layer: obtained from bio-based acrylate adhesive 1, with a thickness of 10 μm and a bio-based content of 75%;

[0159] 5) Second release film: made of PCR PET, with a thickness of 23 μm.

[0160] The bio-based conductive tape 1 of the present invention has a gray appearance and a thickness of 123 μm.

[0161] Example 2 Bio-based acrylate adhesive 2 and bio-based conductive tape 2

[0162] According to the preparation method of Example 1, a bio-based acrylate adhesive 2 and a bio-based conductive tape 2 are obtained, the difference being that different acrylate monomers are selected.

[0163] Example 3 Adhesive 3 and Conductive Tape 3

[0164] Same as Example 1, except that all raw materials are from non-sustainable sources.

[0165] Example 4 Bio-based acrylate adhesive 4 and bio-based conductive tape 4

[0166] Same as Example 1, except that the types and amounts of some components in the composition are different.

[0167] Example 5 Bio-based acrylate adhesive 5 and bio-based conductive tape 5

[0168] Same as Example 1, except that the amount of conductive filler used is different.

[0169] Comparative Example 1 Acrylate Adhesive C1 and Conductive Tape C1

[0170] Same as Example 1, except that 2-OA (2-octyl acrylate) in Example 1 is replaced by i-OA (isooctyl acrylate, structural formula: ) and all raw materials are from non-sustainably sourced materials.

[0171] Comparative Example 2 Acrylic Adhesive C2 and Conductive Tape C2

[0172] Same as Example 1, except that the n-HA (n-heptyl acrylate) in Example 2 is replaced by 2-EHA (2-ethylhexyl acrylate, structural formula: ) and all raw materials are from non-sustainably sourced materials.

[0173] The relevant data of Examples 1-5 and Comparative Examples 1-2 are shown in Table 1.

[0174] Table 1

[0175]

[0176] From Table 1, we can see that:

[0177] 1) By comparing the conductive tape 1 of Example 1 and the conductive tape C1 of Comparative Example 1, it can be seen that: compared with the conductive tape C1 using i-OA (isooctyl acrylate) as the core monomer, the peeling force of the conductive tape 1 using 2-OA (2-octyl acrylate) as the core monomer is significantly increased by 16% (=10.5-9.0) / 9.0), that is, it has better adhesion performance, and the contact resistance is significantly smaller, which is reduced by 50% (=(0.08-0.04) / 0.08), that is, it has better conductive performance;

[0178] 2) Comparative Example 2 uses 2-EHA (2-ethylhexyl acrylate) which is often used in the prior art as the core monomer. The obtained conductive tape C2 is compared with Example 2 of the present application. It can be seen that the conductive tape 2 using the acrylate monomer as the core monomer of the present application has a higher peel force, that is, has a better adhesive performance, and has a lower contact resistance, that is, has a better conductive performance;

[0179] 3) It can be seen from Examples 1 and 3 that the conductive tape obtained by the adhesive composition of the present application can obtain excellent conductive properties and adhesive properties regardless of whether it is made of conventional non-sustainable source materials or sustainable source materials of the present invention;

[0180] In other words, the material origin of the raw materials (non-sustainably sourced materials vs. sustainably sourced materials) has no effect on the conductive properties and adhesive properties of the conductive tape.

[0181] 4) It can be seen from Examples 1-5 that the conductive tapes prepared by using the composition selection and specific dosage range of the present invention can obtain excellent conductive properties and adhesive properties.

[0182] All documents mentioned in the present invention are cited as references in this application, just as each document is cited as reference individually. In addition, it should be understood that after reading the above teachings of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

Claims

1. A conductive adhesive composition, characterized in that: The composition comprises the following components: The acrylate monomer comprises a first monomer and a second monomer; The first monomer has a structure shown in Formula I: Wherein, R1 is H or C1-C3 alkyl; R2 is a C6-C8 alkyl group, and the C6-C8 alkyl group is a straight-chain alkyl group; The second monomer is selected from the following group: a compound represented by formula II, a compound represented by formula III, or a combination thereof; R4 is selected from the following groups: H, unsubstituted or C1-C3 alkyl-substituted C3-C8 cycloalkyl, C1-C6 alkyl; R5 is a 4-8 membered heterocyclic group containing 1, 2 or 3 heteroatoms selected from N, O or S; Furthermore, based on the total weight of the acrylic ester monomer, the content of the first monomer is 55-75 wt %.

2. The conductive adhesive composition according to claim 1, wherein: R1 is selected from the group consisting of H, methyl, ethyl, propyl, isopropyl.

3. The conductive adhesive composition according to claim 1, wherein: R2 is selected from the group consisting of n-hexyl, n-heptyl, and n-octyl.

4. The conductive adhesive composition according to claim 1, wherein: The first monomer is selected from the group consisting of:

5. The conductive adhesive composition according to claim 1, wherein: The second monomer is selected from the group consisting of:

6. The conductive adhesive composition according to claim 1, wherein: The cross-linking agent is selected from the group consisting of ethylene glycol dimethacrylate, 1,6-hexanediol diacrylate, and neopentyl glycol polymethylethylene oxide diacrylate; The tackifier is selected from the group consisting of rosin resin, terpene resin, and C5-C9 petroleum resin; The conductive filler is selected from the following group: particles of nickel, iron, chromium, cobalt, aluminum, copper, silver, gold, vanadium, tin, titanium, or niobium or their alloys; solder; stainless steel; metal oxides; carbon black; metal-coated particles obtained by coating the surface of metal-coated polymer microbeads or glass microbeads; and conductive particles of other metals coated on the surface of metal particles.

7. A conductive tape, characterized in that: The adhesive tape comprises the following structures in sequence: 1) an optional first release film; 2) a first adhesive layer; 3) substrate; 4) a second adhesive layer; 5) an optional second release film; The first adhesive layer and the second adhesive layer are made of the conductive adhesive composition according to claim 1.

8. The conductive tape according to claim 7, characterized in that: The thickness of the adhesive tape is 20-150 μm.

9. The conductive tape according to claim 7, characterized in that: The peeling force of the adhesive tape is ≥8.5N / cm; and / or The contact resistance of the adhesive tape is ≤0.06Ω.

10. The use of the conductive tape according to claim 7, characterized in that: Used for bonding components in electronic products.